Inovasi Jasa Re – Design Packaging Dengan Jasa Kilat Untuk Membantu Pembisnis Oleh Mahasiswa Wirausaha Merdeka Universitas 17 Agustus 1945 Surabaya - Zayna Faisa Amel; Hetti Sari Ramadhani (International Forum of Researchers and Lecturers, 2024)
Independent Entrepreneurship is one of the Independent Campus Learning (MBKM) programs offered by the Ministry of Education, Culture, Research and Technology. This program provides an opportunity for students to add and hone soft skills through learning outside the lecture classroom.The aim of this program is to provide opportunities for students to add and hone soft skills through learning outside the lecture classroom, Providing in-depth insight into the world of business and economics, understanding business processes, markets, competition, as well as factors that influence business success.The expected results of the independent entrepreneurship program are to stimulate student creativity and innovation, so that students can develop ideas and solutions about business, as well as making prototypes. others as well as increasing sales and so on at affordable prices and manufacturing with minimum possible time.